The nowhere office : reinventing work and the workplace of the future - Hobsbawm, Julia (PublicAffairs, 2022)
"What has changed in the workplace? Everything. The traditional office was probably doomed anyway. Then a global shutdown changed everything we thought we knew about work, including where and when it needed to take place. Automation and the Fourth Industrial Revolution have accelerated, and perhaps as much as one third of the world's permanent workforce will soon become remote. In The Nowhere Office, Julia Hobsbawm offers a strategic and practical guide to navigating this pivotal moment in the history of work and provides lessons for how both employees and employers can adapt. Hobsbawm draws on her extensive networks in business, academia, and entrepreneurship across generations to offer new ideas about how to handle hybrid working, as well as provides deep insight into how the way we work is being transformed by larger issues such as community, hierarchy, bias, identity, and security. The Nowhere Office describes a unique moment in the history of work which, if understood and handled correctly, can provide a springboard for the biggest transformational change in the workplace for a century: something better, more meaningful, and more workable for everyone"--